EFFECT OF WEST SUMATRAN DADIAH ON BODY WEIGHT AND GLYCEMIA IN HYPERGLYCEMIC RATS - Meri Wulandari; Ety Yerizel; Harnavi Harun; Efrida (JURNAL KATALISATOR, 2026)
This study was a laboratory-based experimental study using a post-test control group design to evaluate the effect of curd administration on body weight and blood glucose levels in hyperglycemic rat model. Male Wistar rats (Rattus norvegicus) aged 8–10 weeks with body weights of 250–300g were used and randomly divided into four groups: a negative control group without diabetes induction or treatment, a positive control group with diabetes induction without therapy, and two treatment groups receiving curd at different doses, P1 (1.8750 g/250 g body weight) and P2 (3.750 g/250 g body weight). The mean body weight was 277.67 g in the negative control group and 227.50 g in the positive control group. Treatment groups showed increased body weights of 246.83 g in P1 and 262.50 g in P2. Blood glucose levels were 125.56 mg/dL in the negative control group and increased to 487.00 mg/dL in the positive control group, while curd administration reduced levels to 122.17 mg/dL in P1 and 101.83 mg/dL in P2. These results indicate that curd improves body weight and lowers blood glucose in hyperglycemic rats, with greater effects at higher doses, suggesting its potential as a functional food for metabolic and glycemic control.